(untitled) (Academia Journal of Medicine, 2022)
This narrative review delves into the impact of social media on oral health, examining its influence on awareness and education, the associated challenges and risks, strategies to mitigate negative impacts, and future opportunities. Understanding the multifaceted impact of social media on oral health is crucial for developing effective approaches to leverage its potential and address its pitfalls.